The ASEAN Economic Community: Progress, challenges, and prospects - Siow Yue Chia (Asian Development Bank Institute (ADBI), 2013)
Serious efforts at economic integration among the Association of Southeast Asian Nations (ASEAN) members started only in 1992. Initial obstacles included the widespread pursuit of import substitution policies of industrialization, the small extent of intra-ASEAN trade, and the wide differences in economic size, development level, and industrial competence giving rise to widely divergent perceptions of benefits and costs of integration. The switch to outward-looking development strategies and external pressures (such as the formation of the European Union Single Market and the North American Free Trade Area) pressured ASEAN to form a free trade area (FTA) in 1992. The challenges of globalization, slow recovery from the Asian financial crisis, and the economic rise of the People's Republic of China (PRC) and India further pressured ASEAN into deep integration in 2003 with the formation of the ASEAN Economic Community (AEC). The AEC has objectives of a single market and production base, a competitive economic region, equitable economic development, and integration into the global economy. It involves liberalization and facilitation of trade in goods, services, and investment, as well as protection and promotion of investment; narrowing the development gap; and free flow of skilled labor and freer flow of capital. The AEC Blueprint outlines actions and measures and time lines for completion by the 2015 deadline. However, by end-2011 only an implementation rate of 67.5% had been achieved. While tariff elimination had largely been on schedule, there were difficulties with removal of non-tariff barriers (NTBs) and services and investment liberalization. In summary, the AEC has come a long way, but it has fallen short of the high standard and time frame it has set for itself. ASEAN has to find the political will and management capability to fulfill all goals in the AEC Blueprint and embark on further liberalization, rationalization, and integration to seize the opportunities and successfully meet the economic challenges of the 21st century.
Keywords: F13; F15; O19; O24; 330; regional integration; regional cooperation; economic cooperation; trade; investment; goods; services; asean economic community; Wirtschaftsintegration; Freihandelszone